2014
DOI: 10.1021/jp409660b
|View full text |Cite
|
Sign up to set email alerts
|

Watson–Crick and Sugar-Edge Base Pairing of Cytosine in the Gas Phase: UV and Infrared Spectra of Cytosine·2-Pyridone

Abstract: While keto-amino cytosine is the dominant species in aqueous solution, spectroscopic studies in molecular beams and in noble gas matrices show that other cytosine tautomers prevail in apolar environments. Each of these offers two or three H-bonding sites (Watson-Crick, Wobble, Sugar-edge). The mass-and isomer-specific S 1 ← S 0 vibronic spectra of cytosine·2-pyridone (Cyt·2PY) and 1-methylcytosine·2PY are measured using UV laser resonant twophoton ionization (R2PI), UV/UV depletion and IR depletion spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
(122 reference statements)
2
8
0
Order By: Relevance
“…Our calculations also predict that monohydration of keto‐Cy at site A is more stable than at site B by about 2.0–2.7 kJ mol −1 . This result is consistent with a recent study that experimentally confirmed that 2‐pyridone binds more strongly at site A than at site B of keto‐Cy 53. Because of the lower barriers involved, the distributions of binding‐site isomers are expected to approach those near the low temperature limit (<100 K), suggesting that the Cy⋅H 2 O transient arises mostly (>90 %) from keto‐Cy⋅H 2 O with the water bound at site A .…”
Section: Zero‐point Energy Corrected Relative Energies (δEzpe) and Bosupporting
confidence: 91%
“…Our calculations also predict that monohydration of keto‐Cy at site A is more stable than at site B by about 2.0–2.7 kJ mol −1 . This result is consistent with a recent study that experimentally confirmed that 2‐pyridone binds more strongly at site A than at site B of keto‐Cy 53. Because of the lower barriers involved, the distributions of binding‐site isomers are expected to approach those near the low temperature limit (<100 K), suggesting that the Cy⋅H 2 O transient arises mostly (>90 %) from keto‐Cy⋅H 2 O with the water bound at site A .…”
Section: Zero‐point Energy Corrected Relative Energies (δEzpe) and Bosupporting
confidence: 91%
“…1mCy exists predominately as the keto form in the gas phase, and as such, 1mCy has often been used to identify the keto contributions in Cy tautomeric mixtures. [12,53,54] Thepresumption that the excited-state energetics and dynamics of 1mCy closely resemble those of keto-Cy has been discussed previously [12,54] and is supported by more recent theoretical studies. [14,15] As shown in Figure 2, the 1mCy monomer transient does exhibit the characteristic 0.5 ps decay of keto-Cy at 267 nm excitation.…”
supporting
confidence: 58%
“…[52] Our calculations also predict that monohydration of keto-Cy at site A is more stable than at site B by about 2.0-2.7 kJ mol À1 .T his result is consistent with arecent study that experimentally confirmed that 2-pyridone binds more strongly at site A than at site B of keto-Cy. [53] Because of the lower barriers involved, the distributions of binding-site isomers are expected to approach those near the low temperature limit (< 100 K), suggesting that the Cy•H 2 O transient arises mostly (> 90 %) from keto-Cy•H 2 Ow ith the water bound at site A.A ni mmediate conclusion is that monohydration of keto-Cy at site A does not alter its excitedstate deactivation dynamics much, because the decay time is essentially the same as that of keto-Cy monomer at the same excitation energy.…”
mentioning
confidence: 99%
“…68,70 This finding suggests for the GC base pair, that the triply H-bonded Watson-Crick base pair has much faster internal conversion than other GC cluster structures and that for GG and CC dimers the lowest energy, symmetrically Hbound, structures exhibit short excited state lifetimes as well. 37,[117][118][119][120][121] For the GC base pair, Domcke and Sobolewski predict a rapid internal conversion following coupling with a charge transfer state, which causes a proton transfer of the central hydrogen from G to C. 122 The chargetransfer state couples with the ground state with a CI leading to a return of the proton to the guanine, completing the deactivation. A similar process may occur in intramolecularly hydrogen bonded nucleosides.…”
Section: Hydrogen Bonding / Charge Transfermentioning
confidence: 99%